A new species of the genus Pseudochorthippus Defaut, 2012 (Orthoptera: Acrididae: Gomphocerinae) from southeastern Kazakhstan, closely related to Pseudochorthippus turanicus (Tarbinsky, 1925), comb. nov. - Tishechkin, Dmitri Yu.; Vedenina, Varvara (Zootaxa, 2025)
Pseudochorthippus turanicus (Tarbinsky, 1925) comb. nov. is redescribed and illustrated based on specimens from southeastern Kazakhstan and northern Kyrgyzstan and the type series deposited in the collection of the Zoological Museum of Moscow State University; lectotype of this species is designated. P. iliensis sp. nov. from the Ili River basin, Southwestern Balkhash region, Kazakhstan, closely related to P. turanicus in morphological characters, but distinctly differing from it in the calling song pattern, is described. Oscillograms of songs of four species of the genus Pseudochorthippus occurring in southern Kazakhstan are presented.